2022
DOI: 10.3390/cells11101678
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells as Biomarkers of Cardiovascular Pathologies: A Narrative Review

Abstract: Endothelial progenitor cells (EPC) may influence the integrity and stability of the vascular endothelium. The association of an altered total EPC number and function with cardiovascular diseases (CVD) and risk factors (CVF) was discussed; however, their role and applicability as biomarkers for clinical purposes have not yet been defined. Endothelial dysfunction is one of the key mechanisms in CVD. The assessment of endothelial dysfunction in vivo remains a major challenge, especially for a clinical evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 125 publications
1
20
0
7
Order By: Relevance
“…Previous studies have shown that eNOS is activated via the PI3K/Akt/eNOS and Rho/ROCK pathways [17,[24][25][26][27]. Moreover, statins cause phosphorylation of Akt in the PI3K/Akt/eNOS pathway [16,18,[28][29][30]. In the current study, statin-induced increase in eNOS expression in the intimal epithelium was thought to mediate these pathways.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Previous studies have shown that eNOS is activated via the PI3K/Akt/eNOS and Rho/ROCK pathways [17,[24][25][26][27]. Moreover, statins cause phosphorylation of Akt in the PI3K/Akt/eNOS pathway [16,18,[28][29][30]. In the current study, statin-induced increase in eNOS expression in the intimal epithelium was thought to mediate these pathways.…”
Section: Discussionmentioning
confidence: 48%
“…Endothelial nitric oxide synthase (eNOS), which is expressed specifically in vascular endothelial cells, is primarily associated with the production of the vasoactive substance nitric oxide (NO), and is an important factor when assessing endothelial cell function [12][13][14][15]. Previous studies have shown that statins are associated with the expression of eNOS mediated by Akt [16][17][18]. CAWS vasculitis has also been speculated to induce cellular senescence of vascular endothelial cells, leading to suppression of eNOS [19].…”
Section: Introductionmentioning
confidence: 99%
“…They have proliferative and angiogenic potential and have been implicated in endothelial repair [23]. There are several evidence showing that CEC levels are increased in cardiovascular diseases and correlate with endothelial dysfunction and inflammatory markers such as C-reactive protein [25,26]. On the other hand, literature shows an inverse correlation between the number of EPC and the presence of atherosclerosis and cardiovascular dysfunction in human subjects [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…During exercise, the increase (↑) in cardiac output and blood flow to active muscles increase the exercise-induced shear stress that stimulates the endothelial cells to increase the activity of endothelial nitric oxide synthase (eNOS) and produce higher amounts of nitric oxide (NO) [ 42 ]. The increase in NO [ 42 , 47 , 48 ], hypoxia-inducible factor (HIF)-1 and -2, erythropoietin (EPO) [ 25 ], and other angiogenic growth factors or chemokines, namely the vascular endothelial growth factor (VEGF), angiopoietin and stromal cell-derived factor (SDF)-1 bonding with the chemokine receptor (CXCR-4) [ 49 , 50 ] seem to mediate the mobilization of EPCs from bone marrow to peripheral blood [ 25 ]. The figure was designed by using the BioRender.com resource.…”
Section: Figurementioning
confidence: 99%